Non-targeted Metabolomics Reveals Metabolic Characteristics of Porcine Atretic Follicles - Mo, Jiayuan; Sun, Le; Cheng, Juanru; Lu, Yujie; Wei, Yaochang; Qin, Guangsheng; Liang, Jing; Lan, Ganqiu (Frontiers in Veterinary Science, 2021)
Follicular atresia is one of the main factor limiting reproduction power of domestic animals. At present, the molecular mechanisms involved in atresia at the metabolism level remain incompletely understood. The purpose of this study was to investigate the metabolic characteristics of porcine follicles atresia from the perspective of metabolites in follicular fluid (FF). According to morphology of follicle (the appearance of the follicle, the state of cumulus oocyte complexs (COCs) and granulosa cells (GCs)), this study divided the follicles into healthy follicle (HF) and atretic follicle (AF). The expression of genes related to atresia in GCs and concentration of estradiol (E2) and progesterone (PROG) in FF from HF and AF were retrospectively measured to confirm the follicle classification. Then we used the liquid chromatography-mass spectrometry (LC-MS) based non-targeted metabolomics approach for the first time to analyze FF of healthy and atresia follicles in Bama Xiang pig. The results showed that the content of E2 in FF were significantly reduced in AF as compared to HF, whereas PROG were significantly increased. The expression of BCL2, VEGFA and CYP19A1 genes in HF were significantly higher than AF. By contrary BAX and Caspase3 genes were significantly lower in HF. 18 different metabolites were found in metabolomics data and were involved in 12 metabolic pathways. These findings indicate that the metabolic alterations of during follicles atresia in Bama Xiang pig which mainly involved lipids, amino acids and bile acids metabolism, may be related to the underlying mechanism of follicular atresia in porcine.